PENGARUH KOMPETENSI, DISIPLIN DAN KOMPENSASI NON FINANCIAL TERHADAP KINERJA GURU PADA BEBERAPA SMA NEGERI DI PARIGI MOUTONG (Studi Perbandingan Guru Tersertifikasi dengan Belum Tersertifikasi) - Hapsa, Hapsa (Katalogis, 2015)
The objective of this research are to know and analyze the effects of competency, discipline and non-financial compensation on teacher’s performance at public senior high school in Parigi Moutong (a comparison study between certified and un-certified teacher), and to know the difference between performance of certified and un-certified teacher. This research has been conducted in public senior high school 1 Ampibabo, public senior high school 1 Palasa, and public senior high school 1 Bolano Lambunu involving 80 respondents. The study employs multiple linear regressions to test the relationship between dependent and independent variables using significant level α ≤ 0.05 with SPSS program version 16. corrected item total correlation technique has been used as validity test with minimum limit r > 0,3 and cronbach alpha has been use as reliability test with minimum coefficient α > 0.6. The result show that competency, discipline and non-financial compensation perform significant effects on teacher’s performance at public senior high school with adjusted R-square value 0.493. It means that 49,3 % teacher’s performance is effected by competency, discipline and non-financial compensation, and the rest is affected by other variables that are not investigated in this research. In addition, there is no significant difference between performance of certified and un-certified teacher.